2013
DOI: 10.1016/j.apenergy.2013.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the configuration of a façade module for office buildings by means of integrated thermal and lighting simulations in a total energy perspective

Abstract: Integrated thermal-daylighting simulations on a low energy building are performed. Optimal WWR of the façade that minimize the total energy demand is searched. Optimal WWR were found in the range 35-45%, regardless the orientation. If state-of-the-art technologies are used, WWR play a crucial role (maximum influence: 11%). The optimal configurations are tested against different building geometries and HVAC efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 24 publications
1
72
0
2
Order By: Relevance
“…However, from a thermal point of view, it is not always preferable to design a facade with a large number of windows, as windows are often a weak point of thermal resistance owing to their large thermal transmittance (i.e., U-value) compared to other building envelope components (walls, roof, and floor). Many previous studies have investigated the energy performance of windows [2][3][4][5][6]. Currently, the most popular glazing system is double glazing, which balances both performance and cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, from a thermal point of view, it is not always preferable to design a facade with a large number of windows, as windows are often a weak point of thermal resistance owing to their large thermal transmittance (i.e., U-value) compared to other building envelope components (walls, roof, and floor). Many previous studies have investigated the energy performance of windows [2][3][4][5][6]. Currently, the most popular glazing system is double glazing, which balances both performance and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Kheiri [27] found the optimal value in the range of 20-32% for a building that was featured by a low-performance façade (U values for windows and walls were 2.4 W/m 2 K and 2.6 W/m 2 K respectively) and had no shading system. However, Goia et al [28] found the optimal value in the range of 35-45% through the integration of external solar shading devices with a high-performance façade (U values for windows and walls were 0.7 W/m 2 K and 0.15 W/m 2 K respectively). Therefore, it can be inferred that the optimal WWR value depends on the envelope properties employed in the simulations and can influence the results to some extent.…”
Section: Window-to-wall Ratio and Building Energy Performancementioning
confidence: 99%
“…However, Goia et al [28] found the optimal value in the range of 35-45% through the integration of external solar shading devices with a high-performance façade (U values for windows and walls were 0.7 W/m 2 K and 0.15 W/m 2 K respectively). Therefore, it can be inferred that the optimal WWR value depends on the envelope properties employed in the simulations and can influence the results to some extent.…”
Section: Window-to-wall Ratio and Building Energy Performancementioning
confidence: 99%
“…Several studies have been performed where control strategies and patterns of various shading systems have been studied (Tzempelikos and Athienitis 2007;Koo et al 2010;Appelfeld et al 2012;Goia et al 2013). In (van Moeseke et al 2007) it was found that in order to reduce heating demands during winter, a combination of solar irradiance levels and internal temperature set points should be used.…”
Section: Energy Performance Of Shading Systems -Existing Studiesmentioning
confidence: 99%